Jan Čep and Milada Součková: Two Modes of Nostalgia - Hrdlička, Josef (Bohemica Olomucensia, 2015)
The article shortly describes more general aspects of the writing in exile, especially in regard to the concept of nostalgia studied by Jean Starobinski. It examines the nostalgia by Jan Čep and Milada Součková and investigates the conception of "writing for one's self " as an important characteristic not only in exilic writing.
Keywords: Jan Čep; Milada Součková; nostalgia; exilic writing